2006 Canadian Conference on Electrical and Computer Engineering 2006
DOI: 10.1109/ccece.2006.277821
|View full text |Cite
|
Sign up to set email alerts
|

A Technology Review and Simulation Based Performance Analysis of River Current Turbine Systems

Abstract: River Current Turbines are electromechanical energy converters that harness kinetic energy of a stream of flowing river water to generate electricity. Research in this domain is limited and various concepts are emerging only recently. In this paper, an extensive technology survey and comparison of various system options are discussed in order to formulate a basis for further analysis. Simplified mathematical modeling of an augmentation device and Darrieus type rotor has been carried out. Simulations are done i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…A power coefficient reaches 1.22 and is exceeding the Betz limit of 0.59 due to the use of diffuser device. Compared with Ponta (2000) and Khan et al (2006), where a maximum velocity increase factor of 1.67 was reported, the velocity increase factor of 1.22 in ducted waterwheel current turbine with solar-planetary type blades is acceptable.…”
Section: Resultsmentioning
confidence: 92%
“…A power coefficient reaches 1.22 and is exceeding the Betz limit of 0.59 due to the use of diffuser device. Compared with Ponta (2000) and Khan et al (2006), where a maximum velocity increase factor of 1.67 was reported, the velocity increase factor of 1.22 in ducted waterwheel current turbine with solar-planetary type blades is acceptable.…”
Section: Resultsmentioning
confidence: 92%
“…Similar to the situation with tidal currents, however, little has been published regarding the velocity distribution and the possible degree of utilisation. One of few authors to study river current turbines is Khan et al, [21][22][23][24][25] but the focus seems to be more on the technology rather than on the resource. In one of the articles, 23 Khan asks the question what the definition of a resourceful site would be.…”
Section: A Degree Of Utilisationmentioning
confidence: 97%
“…Others are the Blue Energy tidal turbine, a ducted 4-bladed fixed-geometry Darrieus turbine, mounted in a durable concrete marine caisson that acts as a flow concentrator and the Hydro Helix turbine, a system that features a ducted turbine fixed to the seabed via a gravity foundation mentioned in [18]. More discussions on duct augmentation in river/marine applications can be found in [88][89][90]. A survey conducted on all systems working as a speed increaser found that a duct captures a large area of stream and accelerates the flow through a narrowing channel into the turbine.…”
Section: Efficiency Increase Of Turbines In the Worldmentioning
confidence: 99%